Visual-, Olfactory-, and Nectar-Taste-Based Flower Aposematism - Simcha Lev-Yadun (Plants, 2024)
Florivory, i.e., flower herbivory, of various types is common and can strongly reduce plant fitness. Flowers suffer two very different types of herbivory: (1) the classic herbivory of consuming tissues and (2) nectar theft. Unlike the non-reversibility of consumed tissues, nectar theft, while potentially reducing a plant’s fitness by lowering its attraction to pollinators, can, in various cases, be fixed quickly by the production of additional nectar. Therefore, various mechanisms to avoid or reduce florivory have evolved. Here, I focus on one of the flowers’ defensive mechanisms, aposematism, i.e., warning signaling to avoid or at least reduce herbivory via the repelling of herbivores. While plant aposematism of various types was almost ignored until the year 2000, it is a common anti-herbivory defense mechanism in many plant taxa, operating visually, olfactorily, and, in the case of nectar, via a bitter taste. Flower aposematism has received only very little focused attention as such, and many of the relevant publications that actually demonstrated herbivore repellence and avoidance learning following flower signaling did not refer to repellence as aposematism. Here, I review what is known concerning visual-, olfactory-, and nectar-taste-based flower aposematism, including some relevant cases of mimicry, and suggest some lines for future research.